Transcriptomic Analysis of Resistant and Wild-Type Isolates Revealed Fludioxonil as a Candidate for Controlling the Emerging Isoprothiolane Resistant Populations of Magnaporthe oryzae - Wang, Zuo-Qian; Meng, Fan-Zhu; Yin, Liang-Fen; Yin, Wei-Xiao; Lv, Liang; Yang, Xiao-Lin; Chang, Xiang-Qian; Zhang, Shu; Luo, Chao-Xi (Frontiers in Microbiology, 2022)
The point mutation R343W in MoIRR, a putative Zn2Cys6 transcription factor, introduces isoprothiolane (IPT) resistance in Magnaporthe oryzae. However, the function of MoIRR has not been characterized. In this study, the function of MoIRR was investigated by subcellular localization observation, transcriptional autoactivation test, and transcriptomic analysis. As expected, GFP-tagged MoIRR was translocated in the nucleus, and its C-terminal could autonomously activate the expression of reporter genes HIS3 and α-galactosidase in absence of any prey proteins in Y2HGold, suggesting that MoIRR was a typical transcription factor. Transcriptomic analysis was then performed for resistant mutant 1a_mut (R343W), knockout transformant ΔMoIRR-1, and their parental wild-type isolate H08-1a. Upregulated genes in both 1a_mut and ΔMoIRR-1 were involved in fungicide resistance-related KEGG pathways, including the glycerophospholipid metabolism and Hog1 MAPK pathways. All MoIRR deficiency-related IPT-resistant strains exhibited increased susceptibility to fludioxonil (FLU) that was due to the upregulation of Hog1 MAPK pathway genes. The results indicated a correlation between FLU susceptibility and MoIRR deficiency-related IPT resistance in M. oryzae. Thus, using a mixture of IPT and FLU could be a strategy to manage the IPT resistant populations of M. oryzae in rice fields.